2022
DOI: 10.3390/d14030179
|View full text |Cite
|
Sign up to set email alerts
|

Global Medicinal Use of Bats: A Systematic Literature and Social Media Review

Abstract: The hunting of bats for food and medicine is one of the greatest threats to bat conservation. While hunting for consumption is the focus of increased attention, the specific medicinal uses of bats are poorly documented, limiting mitigation efforts. Here, we determine the distribution of bat hunting for food and medicinal use and characterize medicinal use practices. We systematically surveyed English-language scientific literature and social media platforms utilizing keywords and hashtags in 27 languages. We f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
(17 reference statements)
0
7
0
Order By: Relevance
“…H. larvatus is used as a traditional medicine by people in India, China, Malaysia, Pakistan, and Nepal (Tuladhar-Douglas 2008; Riccucci 2012; Lavery 2017). H. larvatus has been used to treat 42 diseases of 11 human body systems in 37 countries and asthma is the most common disease, followed by kidney disease (Tackett et al 2022). H. larvatus is used by people in Bangladesh to treat asthma, arthritis, and fever (Nahar et al 2020) and to increase female fertility in Nigeria (Vora et al 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…H. larvatus is used as a traditional medicine by people in India, China, Malaysia, Pakistan, and Nepal (Tuladhar-Douglas 2008; Riccucci 2012; Lavery 2017). H. larvatus has been used to treat 42 diseases of 11 human body systems in 37 countries and asthma is the most common disease, followed by kidney disease (Tackett et al 2022). H. larvatus is used by people in Bangladesh to treat asthma, arthritis, and fever (Nahar et al 2020) and to increase female fertility in Nigeria (Vora et al 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Topical feathers of H. larvatus to treat burns, and consumption of cooked brains to improve children's intelligence (Paige et al 2014). The body parts of H. larvatus used as medicine are meat, and fluids (blood, bile, and oil) (Tackett et al 2022).…”
Section: Resultsmentioning
confidence: 99%
“…We also collected ectoparasites found in the bodies of bats as part of research sampling. Most people consume these organs because they have been proven effective in treating various diseases, such as asthma and kidney disease (12). Apart from that, we also used blood as one of the research samples because the virus can enter humans through direct contact with infected animal body fluids such as blood, secretions, and mucus.…”
Section: Sample Collectionmentioning
confidence: 99%
“…There were ±86 initial cases reported in several countries, including Taiwan, Thailand, Vietnam, Nepal, Sri Lanka, Japan, Singapore, Malaysia, Cambodia, Saudi Arabia, South Korea, and Indonesia. Ultimately, WHO officially declared Covid19 a pandemic on March Cite this as : 12,2020. It was reported that as many as 634,835 cases and 33,106 deaths worldwide as of March 29, 2020.…”
Section: Introductionmentioning
confidence: 99%
“…This is of grave concern because all extinct LOWFBs were intensively hunted island species (IUCN 2022). LOWFBs are hunted for their meat, perceived medicinal value, ornaments, and even currency ( Jones et al 2010, Wiles & Brooke 2010, Mildenstein et al 2016, Lavery & Fasi 2019, Tackett et al 2022. Bat hunting has a long history in the insular Asia-Pacific region, dating back to prehistory, and is likely of particular importance on islands with depauperate fauna (Hand & Grant-Mackie 2012).…”
Section: Slow Recovery From Persistent or Acute Mortality Eventsmentioning
confidence: 99%